BIO ANALYTICAL METHOD FOR QUANTITATIVE ESTIMATION, PHARMACOKINETIC AND BIOEQUIVALENCE STUDY OF NIZATIDINE NOVEL RAFT GASTRO RETENTIVE FORMULATION USING RP-HPLC - SHANTI SAGAR; NERELLA MOUNIKA; RAMGOPAL APPANI; RAJESHWAR VODETI (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This study presents for the development and validation of RP-HPLC method for the determination of nizatidine in rabbit plasma. Methods: The method was used to perform a pharmacokinetics and bio-equity study to compare a raft gastro-retentive formulation of nizatidine with a marketed formulation. Nizatidine is a competitive H2 receptor antagonist that prescribed for the treatment of different disorders connected with gastric acid production, mainly for nocturnal acid secretion. Twelve New Zealand white rabbits were divided into two groups: one of them receive the new raft formulation that is made up from novel ingredients and the second one receive the marketed raft formulation. Results: The results indicated that the novel raft formulation significantly enhanced the bioavailability of nizatidine, with higher Cmax (230.28±0.61 ng/ml) and AUC0-∞ (1826.17±2.38 ng•h/ml) compared to the marketed formulation (Cmax: 210.Mean Cmax values for esomeprazole were 8±4.5 ng/ml, and Cmax for the metabolite were 6.5±1.9 ng/ml AUC0-∞ was 619.1±21,14 ng•h/ml. Conclusion: Also, the physical characterization demonstrated that, for the raft formulation, the mean resident time (MRT) was higher (7.22 ± 0.014 h) than that of the marketed product (3.17 ± 0.07 h) and suggested a sustained release product. A strong in vitro-in vivo correlation (IVIVC) R² = 0.9162 was confirmed to the predictability of the raft formulations performance